2021
DOI: 10.1371/journal.pone.0246750
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary supplementation with grape seed extract in reproductive hens increases fertility in females but decreases semen quality in males of the F1 generation

Abstract: Genetic selection in parental broiler breeders has increased their susceptibility to metabolic disorders and reproductive dysfunction. We have recently shown that maternal dietary grape seed extract (GSE) supplementation in hens improves fertility parameters, egg quality, oxidative stress in different tissues and the quality of F1 chicks. Here, we analysed the growth and fertility (both female and male) of the F1 generation animals and the quality of their offspring (F2 generation). Eggs issued from hens suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…According to Grandhaye et al. ( 2021 ), the supplementation of synthetic antioxidants like vitamin E and selenium has been shown to enhance fertility in laying hens. Therefore, based on the decreased MDA activity observed in our current study, we can infer that the antioxidative activity is responsible for the improved fertility in laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…According to Grandhaye et al. ( 2021 ), the supplementation of synthetic antioxidants like vitamin E and selenium has been shown to enhance fertility in laying hens. Therefore, based on the decreased MDA activity observed in our current study, we can infer that the antioxidative activity is responsible for the improved fertility in laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are important chemical substances constituting fats and are important aromatic substances or precursors of aromatic substances. Studies have shown that fatty acid metabolism levels and composition affect meat quality and its nutritional value; for example, dodecanoic (C12:0), myristic (C14:0), palmitic (C16:0), stearic (C18:0), linoleic (C18:1), alpha-linolenic (C18:2) and linolenic fatty acids (C18:3) can enhance meat flavors (38)(39)(40)(41). Dodecanoic acid is reported to enhance intramuscular fat deposition and increase the accumulation of myristic and myristoleic acids (C14:1), which may benefit human health (42).…”
Section: Discussionmentioning
confidence: 99%